Biodiversity and specificity of planktonic ciliate communities from the zone of Volga and Kama Rivers confluence - S.V. Bykova; V.V. Zharikov (Учёные записки Казанского университета: Серия Естественные науки)
This paper is devoted to the study of free-living ciliates and generalization of data on their development in the reservoirs of the Volga and Kama confluence zone, i.e., directly in the Kuibyshev Reservoir and in other reservoirs adjacent to its basin considered as sources of the potential diversity of ciliates in the region. The relevance of the study is determined by the need to investigate both hydrological and hydrobiological parameters: ciliates is the most unexplored (compared to phytoplankton or zooplankton) component of plankton. Using the results of our research in 2006–2017, we have identified more than 269 species, of which 144 species occur in the reservoir. The significant heterogeneity of the fauna of the watershed reservoirs is confirmed by the relatively low similarity of the fauna from different water bodies with the strong difference in the composition of dominant species and the slight difference in the composition of background species, as well as by the fact that ?б-diversity is much lower than ?в-diversity. It is very important that the study broadens our understanding of the distribution of rare species (for the Volga-Kama cascade of reservoirs): Leprotintinnus pellucidus (Cleve, 1899) and Pelagovorticella mayeri (Faure-Fremiet, 1920) were previously found only in the delta of the Volga River and North Caspian Sea region. A significant contribution of the Kama fauna to the biodiversity of ciliates in the planktonic community of the reservoir below the confluence zone has been proved, despite the greater similarity of the ciliate fauna in the confluence zone with the Volga fauna. The restructuring of the qualitative composition, general and structural indices of the ciliate community appear in the confluence zone of two rivers along the longitudinal axis. The nature of this restructuring, often associated with deviation of most characteristics of the protozoan community (reduction of the species diversity and quantitative parameters, as well as simplification of the species composition and trophic structure, etc.) in the Volga and Kama Rivers confluence zone, does not allow to consider this community as a unique ecotone at this stage.